Law enforcement training using simulation for locally customized encounters - Kent, Julie A; Hughes, Charles E (Frontiers in Virtual Reality, 2022)
Law enforcement professionals require up to date training for interacting with individuals on the autism spectrum in a manner that facilitates positive citizen response. Although these officers interact with the public regularly, they may only have sporadic interactions with citizens who are not neurotypical. The timing of these interactions is not easy to predict; therefore, it is important to provide regular opportunities to practice contacts with special needs communities. However, in much the same way that it can be difficult to provide regular sessions with other protected groups of people, it is not practical to pull individuals on the autism spectrum to participate in law enforcement training. Role play with neurotypical individuals and classroom training presenting facts about autism do little to prepare these officers for their real-world encounters. Virtual interactions with people on the autism spectrum allow officers to practice techniques without compromising the health and safety of the communities they serve. This paper presents results of a study comparing training through experiences in virtual reality (VR) with video training regarding interactions with individuals on the autism spectrum. Officers in a municipal police department were divided into three groups for continuing training purposes. One group received video training, one group received practice in VR, and one group obtained training in both video and VR. The differences in training did not result in significant differences in training effectiveness. However, subjective data did support the efficacy of practice in a virtual setting. This project addressed three important challenges with training in VR. First, the team needed to define the specifics of behavior and language that the simulated individuals would exhibit. Second, the VR had to be tailored to be relevant to the officers participating. Third and finally, the schedule for training delivery had to minimize the time that officers were away from their assigned duties. Officer feedback on their training experiences indicated the approach to these challenges was well-received.